From Mancession to Shecession: Women's Employment in Regular and Pandemic Recessions - Titan Alon; Sena Coskun; Matthias Doepke; David Koll; Michèle Tertilt (Institute of Labor Economics (IZA), 2021)
We examine the impact of the global recession triggered by the Covid-19 pandemic on women's versus men's employment. Whereas recent recessions in advanced economies usually had a disproportionate impact on men's employment, giving rise to the moniker "mancessions," we show that the pandemic recession of 2020 was a "shecession" in most countries with larger employment declines among women. We examine the causes behind this pattern using micro data from several national labor force surveys, and show that both the composition of women's employment across industries and occupations as well as increased childcare needs during closures of schools and daycare centers made important contributions. While many countries exhibit similar patterns, we also emphasize how policy choices such as furloughing policies and the extent of school closures shape the pandemic's impact on the labor market. Another notable finding is the central role of telecommuting: gender gaps in the employment impact of the pandemic arise almost entirely among workers who are unable to work from home. Nevertheless, among telecommuters a different kind of gender gap arises: women working from home during the pandemic spent more work time also doing childcare and experienced greater productivity reductions than men. We discuss what our findings imply for gender equality in a post-pandemic labor market that will likely continue to be characterized by pervasive telecommuting.
Keywords: D13; E32; J16; J20; 330; COVID-19; pandemics; recessions; business cycle; gender equality; school closures; childcare; gender wage gap